Modernising health care reinventing professions, the state and the public - Kuhlmann, Ellen 1957- (Policy Press, 2006)
Modernising health care: Reinventing professions, the state and the public is a crucial contribution to debates about the rapid modernisation of health care systems and the dynamics of changing modes of governance and citizenship